An analytical review on passenger load and market pattern of Pelangi Air Sdn. Bhd / Zaini Zakaria - Zakaria, Zaini (1991)
Pelangi air was set up to fill the gaps left by Malaysian Airline. Started operation with two TwinOtter aircrafts, Pelangi Air is now owns three Dornier 228-200K aircrafts which can accommodate 19 Passenger each. Being a small airline, the company measured the growing rate through the development in the number of passenger carried and load factor. It realises the important of high load factors and good yield management. This research attemps to trace Pelangi air growth since it started operation in 1988. It analyse the pelangi Air passenger growth by evaluating the passenger load and load factors for five selected routes. A market survey was carried out -to determine the market perceptions towards the services provided by the airline. It is hope that the finding of the analysis and market survey can help determine Pelangi Air growth in the coming years.